Effect of gasoline/n-butanol blends on gaseous and particle emissions from an SI direct injection engine. (1st October 2018) - Yu, Xiumin; Guo, Zezhou; He, Ling; Dong, Wei; Sun, Ping; Shi, Weibo; Du, Yaodong; He, Fengshuo
Highlights: The addition of n-butanol can effectively reduce accumulation mode particle number. The addition of n-butanol will increase the nucleation mode particle number. 20% n-butanol blends reach the lowest total particle number under rich mixture. Gasoline/n-butanol blends can effectively reduce the gaseous emissions. The addition of butanol has little influence on IMEP and engine torque. Abstract: N-butanol has shown potential as an alternative fuel to mitigate the energy crisis and reduce emissions. The emission and combustion characteristics of a spark ignition (SI) engine fed with gasoline/n-butanol blends under direct injection are studied in this paper. The experiments are conducted using different excess air ratios (λ) and n-butanol blending volume ratios (NBr). The results indicate that the indicated mean effective pressure (IMEP) and engine torque (Ttq) show small changes following n-butanol addition. The NOx and CO emissions decline continuously with increasing NBr. The n-butanol addition can help reduce HC emissions compared to neat gasoline when the NBr is below 40%; specifically, the HC emissions reach the lowest value at 20% NBr. As for particle emissions, the addition of n-butanol shows a very significant effect on the reduction of accumulation mode particle number, especially at rich-fuel mixture conditions, for which a decrease by about 52% is achieved. On the contrary, the nucleation mode particle number and peak particle diameter increase constantly with increasing NBr. Overall, the addition of 20% NBr to the blends reduces both particle and gaseous emissions. This work therefore presents a procedure to optimize the control of particle and gaseous emissions from gasoline/n-butanol blends, thus reducing the impact of the use of fossil fuel.